Experimental investigation on the effect of shot peening on contact fatigue strength for carburized and quenched gears. (January 2018) - Li, Wei; Liu, Bingshu
Highlights: A gear contact fatigue test method combined with up-down test method and the grouping test method is proposed. An optimized installation scheme for test gears is put forward. The fatigue limit stress values under different reliability are obtained. The confidence level is considered in the procedure of data processing. Shot peening can increase the contact fatigue strength of the 20CrMnMo gears by 14.56%. Abstract: Contact fatigue is one of the main failure modes of the gear. The contact fatigue test of gear is not only an important way to understand the capacity of gear, but also the data base in product design. In order to obtain the contact fatigue characteristics of 20CrMnMo carburized and hardened gears with or without shot peening, this paper presents a method combined with up-down test method and the grouping test method for contact fatigue test of gears. The optimal configuration scheme of gears is also given to obtain experimental data with the least specimens. The R-S-N curves considered confidence level is fitted by the lognormal distribution, to obtain the fatigue limiting stress values under different reliability, which provides the basic test data for the finite life design and high reliability design of the contact fatigue of the gears. The experimental results show that the shot peening treatment can significantly improve the contact fatigue strength of the gear, thus improving the service life.